Individual Ownership and Ex-Dividend Day Price Drop Ratio: Lessons from the US Tax Act 2003 - Barkhordar, Babak; Ahmad, Rubi (Asian Journal of Business and Accounting, 2014)
This study examines the reaction of share prices to firm ownership structure on the ex-dividend day for listed firms in the United States (US) from 2002 to 2010. This period includes the implementation of the US Tax Act 2003, which equalised individual investor tax rates on dividend and capital gains. Using a cross-sectional methodology and market-adjusted model, evidence shows that the average ex-day price drop ratio increases after the US Tax Act 2003. This study also finds evidence that ex-dividend day pricing forms a negative concave function of firms’ individual ownership. This evidence strongly supports the tax-induced dynamic trading theory and is consistent with both tax clientele and short-selling hypotheses. This evidence also reveals that dividend capturing may occur around ex-day, where firms are partially owned by personal shareholders. These findings may be relevant to the Malaysian stocks under the single-tier tax system in Malaysia. Keywords: Ex-Dividend Day Pricing, Individual Ownership, Price Drop Ratio, US Tax Act 2003 JEL Classification: G10, G35